MiR‐329 suppresses the growth and motility of neuroblastoma by targeting KDM1A. Issue 1 (6th December 2013) - Yang, Haifeng; Li, Qi; Zhao, Wohua; Yuan, Dun; Zhao, Hongyang; Zhou, Yong
Abstract : MicroRNAs (miRNAs) act as key regulators of multiple cancers. miR‐329 functions as a tumor suppressor in some malignancies. However, its role in neuroblastoma remains poorly understood. We found that miR‐329 was decreased in metastatic tumor tissues compared with matched primary tumor tissues. Forced overexpression of miR‐329 substantially suppressed cell proliferation, colony formation, migration, and invasion of neuroblastoma cells. Lysine‐specific demethylase 1 (KDM1A) was found to be a target of miR‐329. Furthermore, down‐regulation of KDM1A by shRNA performed similar effects with overexpression of miR‐329. Overexpression of KDM1A partially reversed the tumor suppressive effects of miR‐329 in neuroblastoma cells. Collectively, miR‐329 may suppress neuroblastoma cell growth and motility partially by targeting KDM1A. Abstract : miR‐329 was decreased in metastatic NB. miR‐329 suppressed NB cells viability. miR‐329 inhibited NB cells motility. KDM1A was a target of miR‐329 in NB cells.